Recycled asphalt concrete and preparation method thereof

By adding specific modified materials to the regenerated asphalt concrete, the problem of easy cracking under low temperature conditions is solved, and its crack resistance and durability are significantly improved.

CN119841581AActive Publication Date: 2025-04-18HANZHONG MUNICIPAL HIGHWAY BUREAU

Patent Information

Application Number
CN202510117440.3
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2025-01-24
Publication Date
2025-04-18
Estimated Expiration
2045-01-24

AI Technical Summary

Technical Problem

Recycled asphalt concrete is prone to cracking under low temperature conditions, resulting in its durability not as new asphalt concrete.

Method used

The viscosity, ductility and crack resistance of asphalt are improved by adding hydroxymodified polyester fibers, polymer composite modifiers, modified nanosilica and porous acrylate copolymers to the regenerated asphalt concrete.

Benefits of technology

It improves the low-temperature crack resistance and durability of recycled asphalt concrete, reduces the generation of temperature shrinkage cracks, and enhances the stability of the interface film between asphalt and aggregate.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure BDA0005258148840000131
    Figure BDA0005258148840000131
Patent Text Reader

Abstract

The invention relates to the field of road building materials, and particularly discloses recycled asphalt concrete and a preparation method thereof, and the recycled asphalt concrete comprises the following raw materials: a waste asphalt mixture, matrix asphalt, aggregate, mineral powder, hydroxyl modified polyester fibers, a polymer composite modifier, modified nano silicon dioxide and a regenerant; the preparation method comprises the following steps: preheating the waste asphalt mixture; mixing and preheating the aggregate and the mineral powder; preheating matrix asphalt and mixing the matrix asphalt with the preheated aggregate to prepare a primary mixture; preheating a regenerant, mixing with the primary mixture, and then mixing and stirring with the preheated waste asphalt mixture to obtain a mixture; mixing the hydroxyl modified polyester fiber, the polymer composite modifier and the modified nano silicon dioxide, and then stirring and mixing with the mixture to prepare the recycled asphalt concrete. The method has the characteristics that the later cracking problem of the recycled asphalt concrete is relieved, and the durability of the recycled asphalt concrete is improved.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The present application relates to the field of road construction materials, and more specifically, to a recycled asphalt concrete and a preparation method thereof. Background Art

[0002] With the acceleration of my country's urbanization process and the continuous improvement of transportation infrastructure, asphalt concrete, as the main material for road paving, has an increasing demand year by year. However, the traditional asphalt concrete has a huge demand for natural sand and gravel resources during the production process, which leads to over-exploitation of resources and serious environmental damage. In order to develop green buildings and circular economy, recycled asphalt concrete mixtures are used.

[0003] Recycled asphalt concrete technology is a technology that recycles and processes old asphalt pavement materials and uses them in the preparation of new asphalt concrete. This technology realizes the reuse of resources and is in line with my country's sustainable development strategy. It can make full use of old asphalt pavement materials and reduce dependence on new materials. By recycling waste asphalt concrete, it can reduce resource waste and environmental pollution, and has important economic benefits and social significance.

[0004] Recycled asphalt concrete technology has been applied and developed to a certain extent in my country. At present, the scale of road construction in my country is expanding year by year, and the demand for asphalt concrete mixture is huge. Although the recycled asphalt concrete produced by recycling old materials, crushing, screening, adding regeneration agents and mixing can have similar performance to the original asphalt concrete, and can be widely used in highway, urban road and other engineering construction, there are still some problems that need to be solved in practice. For example, since the recycled asphalt concrete contains a certain proportion of aged asphalt, the light components of the aged asphalt are reduced and the asphaltene is increased, resulting in a decrease in the low-temperature crack resistance of the asphalt, making the recycled asphalt concrete more prone to cracking in the later stage, and its durability is not as good as that of the new asphalt concrete. Summary of the invention

[0005] In order to alleviate the late cracking problem of regenerated asphalt concrete and to improve the durability of regenerated asphalt concrete, the present application provides a regenerated asphalt concrete and a preparation method thereof.

[0006] In the first aspect, the present application provides a recycled asphalt concrete, which adopts the following technical solution: A regenerated asphalt concrete comprises the following raw materials in parts by weight: 80-100 parts of waste asphalt mixture, 10-18 parts of base asphalt, 20-30 parts of aggregate, 5-12 parts of mineral powder, 8-15 parts of hydroxyl modified polyester fiber, 12-18 parts of polymer composite modifier, 3-8 parts of modified nano silicon dioxide and 3-8 parts of regeneration agent; The polymer composite modifier comprises SBS powder and porous acrylic copolymer in a mass ratio of 1:(0.6-0.8), and the modified nano silicon dioxide is obtained by immersing the nano silicon dioxide in an immersion solution containing polyisopropylacrylamide, sodium polystyrene sulfonate, glutamic acid and 2-aminobenzoic acid.

[0007] By adopting the above technical scheme, in this application, waste asphalt concrete is used as the main material, and matrix asphalt and new aggregate are additionally added. The matrix asphalt is used as a binder to form asphalt concrete in combination with new aggregate and waste asphalt concrete. The addition of the regeneration agent can supplement the lost light components of the aged asphalt in the waste asphalt concrete, and can penetrate and dissolve the asphaltene in the aged asphalt, thereby restoring the viscosity and ductility of the asphalt and other indicators, so that it can regain the use performance similar to that of new asphalt, improve the anti-aging performance of asphalt, and improve its durability. In addition, polyester fiber is also added in this application. The addition of polyester fiber can increase the toughness of asphalt concrete on the one hand, improve its crack resistance, and maintain its flexibility and high tensile strength at low temperatures, thereby effectively resisting shrinkage stress and reducing the occurrence of thermal shrinkage cracks; and the three-dimensional distribution and strong adsorption performance of polyester fiber increase the cohesion of asphalt, which can not only form a criss-cross reinforcement and bridging effect in the concrete, effectively improving the high temperature stability of the recycled concrete, but also enhance the ability of the interface film formed between the asphalt and the aggregate in the asphalt concrete to resist the water stripping effect, thereby further improving the late crack resistance of the concrete and improving its durability.

[0008] In the present application, a polymer composite modifier is added, and the addition of SBS powder in the polymer composite modifier can interact with the colloid in the asphalt to form a relatively stable combination. The combination of waste asphalt concrete and regeneration agent allows SBS to not only cross-link with the new matrix asphalt but also restore the cross-linking effect between asphalt and SBS in the waste asphalt concrete, so that the performance of the waste asphalt concrete is as close to the original asphalt level as possible. In addition, the interaction between SBS and asphalt can enhance the bonding force with aggregates, so that the recycled asphalt concrete can still maintain a stable structure under high temperature conditions. The SBS modified asphalt has a higher glass transition temperature and can maintain flexibility and elasticity at low temperatures, significantly improving its performance at low temperatures, thereby reducing the phenomenon of pavement cracking due to temperature changes.

[0009] In addition, modified nano-silica and porous acrylic copolymer are added to the raw materials of the present application. When the modified nano-silica is added to the recycled asphalt concrete, it has a nano-size effect and a high specific surface area, which can significantly improve the mechanical properties and durability of the asphalt material, and it can be evenly dispersed in the asphalt matrix to form a nano-scale reinforcement phase, which significantly improves the elastic modulus and crack resistance of the asphalt, and reduces cracks and damage to the road surface; and after being immersed in an impregnation solution containing polyisopropylacrylamide, sodium polystyrene sulfonate, glutamic acid, etc., the nano-silica is loaded with polyisopropylacrylamide. As a thermosensitive material, it absorbs water and expands in volume when the temperature rises, and releases water and shrinks in volume when the temperature drops, so that the internal stress state of the concrete can be adjusted when the temperature changes, thereby reducing the generation of cracks and improving the durability of the concrete; 2-Aminobenzoic acid contains amino, carboxyl and benzene rings, which react with the hydroxyl groups on the surface of nano-silica through the amino or carboxyl groups, thereby introducing benzene rings. The introduction of benzene ring groups helps to improve the compatibility between nano-silica and asphalt, and also helps to improve the temperature resistance and alleviate cracking caused by thermal shrinkage. The addition of sodium polystyrene sulfonate and glutamic acid, on the one hand, due to the negative charge of the sulfonate group, the sodium polystyrene sulfonate molecules are adsorbed onto the surface of nano-silica with positive charge or adsorption sites on the surface, so that the surface of the nano-silica is covered by the sodium polystyrene sulfonate molecules, forming a steric hindrance effect, thereby reducing the agglomeration of nano-silica and improving its uniform dispersion in asphalt concrete. , which can play a better reinforcing role. On the other hand, the sulfonic acid group in sodium polystyrene sulfonate can also form electrostatic effects and chemical bonds with amino groups such as 2-aminobenzoic acid and glutamic acid to form sulfonamide bonds, and the carboxyl groups in glutamic acid and 2-aminobenzoic acid can also form chemical reactions with the hydroxyl groups in hydroxy-modified polyester fibers. In this way, the polymer composite modifier forms a macromolecular network structure with polyester fibers and nano-silica, further realizing the anti-cracking performance of asphalt concrete and improving its durability. In addition, the modified nano-silica reduces its agglomeration through the steric hindrance effect, and the introduced benzene ring improves its compatibility with asphalt, thereby improving the mechanical properties and durability of the final asphalt concrete.

[0010] The addition of porous acrylate copolymers, on the one hand, utilizes its bonding properties to help the mutual adhesion between aggregates and asphalt, and helps to reduce the generation and expansion of cracks in the recycled asphalt concrete during stress. On the other hand, the acrylate copolymers themselves have high flexibility and can absorb and disperse the stress generated by external forces on the recycled asphalt concrete. Moreover, the formation of pore structures in acrylate copolymers can achieve water storage and release functions to a certain extent. In this way, they can be combined with the thermosensitive substance polyisopropylacrylamide to adjust stress to reduce cracking caused by temperature shrinkage, thereby improving the crack resistance and durability of the recycled asphalt concrete.

[0011] Optionally, the impregnation solution comprises the following raw materials in parts by weight: 10-20 parts of polyisopropylacrylamide, 3-8 parts of sodium polystyrene sulfonate, 2-5 parts of glutamic acid and 6-10 parts of 2-aminobenzoic acid, 15-20 parts of methanol and 8-15 parts of water.

[0012] Optionally, the modified nano-silica is prepared by the following method: Mix polyisopropylacrylamide, sodium polystyrene sulfonate, glutamic acid and 2-aminobenzoic acid with methanol and water, heat to 45-50°C, stir until completely dissolved, then add nano-silica under stirring, stir and pressurize to 0.4-0.6MPa, then immerse for 20-30 minutes, filter and dry to obtain modified nano-silica.

[0013] By adopting the above technical solution, the impregnation modification is carried out under the temperature and pressure conditions of the present application, which helps to promote the modifier molecules in the impregnation liquid to better penetrate into the micropores on the surface of the nano-silicon dioxide, thereby enhancing the interaction between the modifier and the nano-silicon dioxide.

[0014] Optionally, the porous acrylic copolymer is prepared by the following method: 1) Mixing γ-methacryloxypropyltrimethoxysilane, solvent A and graphene aerogel, impregnating and drying to obtain pretreated aerogel; 2) Mixing acrylate monomer, sodium styrene sulfonate, triethanolamine, acrylamide, initiator, crosslinker, stabilizer, toluene and solvent B to prepare a reaction solution, then adding the pretreated aerogel prepared in step 1), polymerizing at 80-90° C. for 2-4 hours to obtain an acrylate copolymer.

[0015] By adopting the above technical scheme, in the present application, γ-methacryloxypropyltrimethoxysilane is first used to pretreat the graphene aerogel, and the trimethoxysilyl group in the γ-methacryloxypropyltrimethoxysilane is hydrolyzed to generate a silanol group, which reacts with the graphene aerogel containing a hydroxyl group to form a silicon-oxygen bond, thereby realizing the introduction of unsaturated double bond groups on the surface of the graphene aerogel, and then after mixing with the reaction solution, under the action of an initiator, the double bond unsaturated groups thereof are in-situ polymerized with acrylate monomers and monomers such as acrylamide using the graphene aerogel as a skeleton to form an acrylate resin, and toluene is added to the reaction solution to achieve the establishment of a pore structure of the acrylate copolymer, and finally the graphene aerogel is obtained. The gel has a skeleton structure and is polymerized in situ to form an acrylic resin. The graphene aerogel itself has the characteristics of high specific surface area and a large number of micropores and hollow structures. The addition of porogens during in-situ polymerization forms an acrylic resin with a porous structure. The formation of the porous structure helps to absorb and disperse stress, and helps to resist the damage of external stress, thereby delaying the generation and expansion of cracks and reducing the risk of crack generation. On the other hand, the establishment of a porous structure can slow down the thermal expansion and contraction of the material and reduce cracks caused by thermal contraction. In addition, the functional monomer introduces sulfonic acid groups and other groups during the compounding process, so that it has a certain water storage function. Combined with temperature-sensitive materials, it can further resist cracking caused by thermal expansion and contraction and improve its durability.

[0016] Optionally, during the preparation of the porous acrylate copolymer, the raw materials are added according to the following weight parts: 3-7 parts of γ-methacryloxypropyltrimethoxysilane, 30-40 parts of solvent A, 25-35 parts of graphene aerogel, 40-50 parts of acrylate monomer, 10-20 parts of sodium styrene sulfonate, 5-12 parts of triethanolamine, 12-22 parts of acrylamide, 2-6 parts of Initiator, 1-3 parts of cross-linking agent, 1-3 parts of stabilizer, 5-10 parts of toluene, 40-50 parts of solvent B.

[0017] By adopting the above technical scheme, the introduction of sulfonic acid groups in sodium styrene sulfonate in the present application realizes the adjustment of the hydrophilic groups of the acrylate copolymer, and also introduces benzene ring groups to improve its compatibility with the asphalt matrix in the present application, while the introduction of hydroxyl and amino functional groups in triethanolamine and acrylamide facilitates the chemical bonding with modified nano-silica and hydroxyl-modified polyester fibers, and finally achieves chemical entanglement of the above substances to form a tighter and firmer network structure, which facilitates the subsequent formation of microcracks and improves durability.

[0018] Optionally, the stabilizer is polyvinyl pyrrolidone or polyethylene glycol; The acrylic acid ester monomer is selected from one or more of methyl methacrylate, ethyl acrylate, isobutyl acrylate, and 2-ethylhexyl acrylate; The initiator is selected from one or both of benzoyl peroxide and azobisisobutyronitrile; The crosslinking agent is selected from one or both of ethylene glycol dimethacrylate and trimethylolpropane triacrylate.

[0019] Optionally, in step 1), solvent A is a mixture of methanol and water in a mass ratio of 1:(1.5-2); The solvent B in step 2) is a mixture of water and sodium dodecyl sulfate in a mass ratio of 1:(0.1-0.2).

[0020] Optionally, the hydroxy-modified polyester fiber is prepared by the following method: The polyester fiber scraps and glass fiber are mixed in a mass ratio of 1: (0.1-0.2) to obtain mixed fibers, and then the mixed fibers are immersed in hydrogen peroxide at a temperature of 50-60° C., and after immersion for 10-20 minutes, hydroxyethyl acrylate and methyl methacrylate are added, and the mixture is reacted at 65-75° C. for 1-2 hours, and then cooled, filtered, washed and dried to obtain hydroxyl-modified polyester fibers.

[0021] By adopting the above technical scheme, in the present application, the mixed fiber is first immersed in hydrogen peroxide, and hydrogen peroxide is used as an oxidant to initiate an oxidation reaction on the surface of the polyester fiber to generate free radical sites. These free radical sites have high reactivity and can undergo addition reactions with double bonds in the monomers to achieve monomer grafting. Then, after hydroxyethyl acrylate and methyl methacrylate are added, the hydroxyl functional groups in hydroxyethyl acrylate react with free radicals on the surface of the polyester fiber, thereby introducing hydroxyl groups into the polyester fiber. Methyl methacrylate and hydroxyethyl acrylate form copolymer segments containing hydroxyl groups through copolymerization, which further react with active sites on the surface of the polyester fiber, so that the hydroxyl groups are more firmly grafted on the fiber, thereby achieving hydroxyl modification of the polyester fiber.

[0022] Optionally, during the preparation of hydroxy-modified polyester fibers, the mass ratio of the mixed fibers to hydrogen peroxide is 1:(1-2), and the mixed fibers are soaked after hydrogen peroxide and water are mixed in a mass ratio of 1:(3-4), and the mass ratio of the mixed fibers to hydroxyethyl acrylate and methyl methacrylate is 1:(0.4-0.5):(0.1-0.2).

[0023] Optionally, the regeneration agent includes mesophase asphalt, tung oil, penetrant, light stabilizer and antioxidant in a mass ratio of 1: (1.5-2): (0.05-0.1): (0.05-0.1): (0.05-0.1).

[0024] By adopting the above technical scheme, in the regeneration agent of the present application, on the basis of tung oil, an intermediate phase asphalt is also added, and the intermediate phase asphalt contains aromatic hydrocarbons and unsaturated double bonds. The addition of the above intermediate phase asphalt introduces unsaturated double bonds and aromatic hydrocarbons, which on the one hand helps to dissolve waste asphalt, and on the other hand can enhance the adhesion and consistency of the asphalt mixture, and the above substances can also react with the oxidized substances in the waste asphalt to achieve the regeneration of asphalt, especially the introduction of hydroxyl and amino groups in the modified silica and polymer modifier in the present application, which serve as reducing functional groups, help to restore the performance of asphalt, and can also chemically react with the oxidized substances in the waste asphalt to improve its molecular structure, achieve asphalt regeneration, and finally obtain regenerated asphalt concrete with better performance.

[0025] Optionally, the matrix asphalt is selected from one or more of petroleum asphalt and natural asphalt; The aggregate is selected from slag and crushed stone in a mass ratio of 1:(2-3), and the crushed stone is selected from crushed stone with a continuous particle size of 5-15 mm.

[0026] Optionally, the antioxidant is 2,2-methylenebis-(4-methyl-6-tert-butylphenol); The light stabilizer is a hindered amine light stabilizer; The penetrant is selected from alkylphenol polyoxyethylene ether.

[0027] By adopting the above technical scheme, hindered amine light stabilizers help to improve the light aging resistance of recycled asphalt and extend its service life. Alkylphenol polyoxyethylene ether has excellent permeability and surface activity, which not only helps to improve the miscibility of the regeneration agent with the waste asphalt mixture and realize the regeneration of waste asphalt, but also helps to improve the miscibility of waste asphalt with new asphalt.

[0028] In a second aspect, the present application provides a method for preparing recycled asphalt concrete, which adopts the following technical solution: A method for preparing regenerated asphalt concrete comprises the following steps: S1. Preheating the waste asphalt mixture at 110-130° C. for 10-20 min to obtain a preheated waste asphalt mixture; The aggregate and the mineral powder are mixed and preheated at 120-150°C for 5-10 minutes to obtain preheated aggregate; S2, preheating the base asphalt at 140-160°C for 5-10 minutes and mixing it with the preheated aggregate to prepare a primary mixture; S3, preheating the regeneration agent at 110-120°C for 3-8 minutes and then mixing it with the primary mixture, and then mixing it with the preheated waste asphalt mixture to obtain a mixture; S4. Mix the hydroxyl-modified polyester fiber, the polymer composite modifier and the modified nano-silicon dioxide and stir them with the mixture to obtain recycled asphalt concrete.

[0029] By adopting the above technical solution, the method provided by the present application is simple, convenient and easy to realize industrialization.

[0030] In summary, this application has the following beneficial effects: 1. The raw materials of the present application are added with modified nano-silica and porous acrylate copolymer. When the modified nano-silica is added to the recycled asphalt concrete, it has a nano-size effect and a high specific surface area, which can significantly improve the mechanical properties and durability of the asphalt material, and it can be evenly dispersed in the asphalt matrix to form a nano-scale reinforcement phase, which significantly improves the elastic modulus and crack resistance of the asphalt, and reduces cracks and damage to the road surface; and after being immersed in an impregnation solution containing polyisopropylacrylamide, sodium polystyrene sulfonate, glutamic acid, etc., the nano-silica is loaded with polyisopropylacrylamide. As a thermosensitive material, it absorbs water and expands in volume when the temperature rises, and releases water and shrinks in volume when the temperature drops, so that the internal stress state of the concrete can be adjusted when the temperature changes, thereby reducing the generation of cracks and improving the durability of the concrete; 2. In the modified nano-silica of the present application, 2-aminobenzoic acid reacts with the hydroxyl group on the surface of the nano-silica through the amino group or the carboxyl group, thereby introducing a benzene ring. The introduction of the benzene ring group helps to improve the compatibility between the nano-silica and asphalt, and also helps to improve the temperature resistance and alleviate the cracking caused by temperature shrinkage; and the addition of sodium polystyrene sulfonate and glutamic acid reduces the agglomeration of the nano-silica and improves its uniform dispersion in the asphalt concrete, which can play a better reinforcing role, and enables the polymer composite modifier to form a macromolecular network structure with the polyester fiber and the nano-silica, further realizing the anti-cracking performance of the asphalt concrete and improving its durability. In addition, the modified nano-silica reduces its agglomeration through the steric hindrance effect, and the introduced benzene ring improves the compatibility with asphalt, thereby improving the mechanical properties and durability of the final asphalt concrete; 3. The addition of porous acrylate copolymer in the present application, on the one hand, utilizes its bonding properties to help the mutual adhesion between aggregate and asphalt, and helps to reduce the generation and expansion of cracks in the regenerated asphalt concrete during the stress process. On the other hand, the acrylate copolymer itself has high flexibility and can absorb and disperse the stress generated by external forces on the regenerated asphalt concrete. Moreover, the formation of the pore structure in the acrylate copolymer can realize the water storage and discharge function to a certain extent. In this way, it can be combined with the thermosensitive material polyisopropylacrylamide for stress regulation to reduce the cracking phenomenon caused by temperature shrinkage, thereby improving the crack resistance and durability of the regenerated asphalt concrete. DETAILED DESCRIPTION

[0031] The present application is further described in detail below in conjunction with the examples. It is particularly noted that if no specific conditions are specified in the following examples, the experiments are carried out according to conventional conditions or the conditions recommended by the manufacturer. Unless otherwise specified, the raw materials used in the following examples can be obtained from common commercial sources.

[0032] In the following preparation example, the graphene aerogel is selected from Suzhou Kaifa New Materials Technology Co., Ltd., whose brand is Beike Nano and model is BK2020062720.

[0033] The following Preparation Examples 1-4 are preparation examples of porous acrylic copolymers, Preparation Examples 5-9 are preparation examples of modified nano-silica, and Preparation Examples 10-13 are preparation examples of hydroxyl-modified polyester fibers.

[0034] Preparation Example 1 A method for preparing a porous acrylic copolymer comprises the following steps: 1) Mix 5 kg of γ-methacryloxypropyltrimethoxysilane, 35 kg of solvent A and 30 kg of graphene aerogel, immerse for 35 minutes and then dry to obtain pretreated aerogel, the immersion temperature is 45° C. 2) 45 kg of acrylate monomer, 15 kg of sodium styrene sulfonate, 8 kg of triethanolamine, 15 kg of acrylamide, 5 kg of initiator, 2 kg of crosslinker, 2 kg of stabilizer, 8 kg of toluene and 45 kg of solvent B were mixed to prepare a reaction solution, and then the pretreated aerogel prepared in step 1) was added, and after polymerization at 85° C. for 3 hours, an acrylate copolymer was obtained.

[0035] Among them, polyvinyl pyrrolidone is selected as the stabilizer; ethyl acrylate is selected as the acrylate monomer; benzoyl peroxide is selected as the initiator; ethylene glycol dimethacrylate is selected as the cross-linking agent; solvent A is selected from a mixture of methanol and water in a mass ratio of 1:1.8; solvent B is selected from a mixture of water and sodium dodecyl sulfate in a mass ratio of 1:0.1.

[0036] Preparation Example 2 A method for preparing a porous acrylic copolymer comprises the following steps: 1) Mix 3 kg of γ-methacryloxypropyltrimethoxysilane, 30 kg of solvent A and 25 kg of graphene aerogel, immerse for 40 minutes and then dry to obtain pretreated aerogel, the immersion temperature is 40° C. 2) 40 kg of acrylate monomer, 10 kg of sodium styrene sulfonate, 5 kg of triethanolamine, 12 kg of acrylamide, 2 kg of initiator, 1 kg of cross-linking agent, 1 kg of stabilizer, 5 kg of toluene and 40 kg of solvent B were mixed to prepare a reaction solution, and then the pretreated aerogel prepared in step 1) was added, and after polymerization at 80° C. for 4 hours, an acrylate copolymer was obtained.

[0037] Among them, polyethylene glycol is selected as the stabilizer; methyl methacrylate is selected as the acrylate monomer; azobisisobutyronitrile is selected as the initiator; trimethylolpropane triacrylate is selected as the cross-linking agent; solvent A is selected as a mixture of methanol and water in a mass ratio of 1:1.5; solvent B is selected as a mixture of water and sodium dodecyl sulfate in a mass ratio of 1:0.1.

[0038] Preparation Example 3 A method for preparing a porous acrylic copolymer comprises the following steps: 1) Mix 7 kg of γ-methacryloxypropyltrimethoxysilane, 40 kg of solvent A and 35 kg of graphene aerogel, immerse for 30 minutes and then dry to obtain pretreated aerogel, the immersion temperature is 50° C. 2) 50 kg of acrylate monomer, 20 kg of sodium styrene sulfonate, 12 kg of triethanolamine, 22 kg of acrylamide, 6 kg of initiator, 3 kg of crosslinker, 3 kg of stabilizer, 10 kg of toluene and 50 kg of solvent B were mixed to prepare a reaction solution, and then the pretreated aerogel prepared in step 1) was added, and after polymerization at 90° C. for 2 hours, an acrylate copolymer was obtained.

[0039] Among them, polyvinyl pyrrolidone is selected as the stabilizer; isobutyl acrylate is selected as the acrylate monomer; benzoyl peroxide is selected as the initiator; ethylene glycol dimethacrylate is selected as the cross-linking agent; solvent A is selected as a mixture of methanol and water in a mass ratio of 1:2; solvent B is selected as a mixture of water and sodium dodecyl sulfate in a mass ratio of 1:0.2.

[0040] Preparation Example 4 A method for preparing a porous acrylic copolymer is carried out according to the method in Preparation Example 1, except that step 1) is not performed, that is, graphene aerogel is not added in step 1).

[0041] Preparation Example 5 A method for preparing modified nano-silicon dioxide comprises the following steps: 15kg of polyisopropylacrylamide, 5kg of sodium polystyrene sulfonate, 3kg of glutamic acid and 8kg of 2-aminobenzoic acid were mixed with 18kg of methanol and 12kg of water, and the mixture was heated to 50°C and stirred until completely dissolved to obtain an impregnation solution. Nano-silica was then added under stirring, stirred and pressurized to 0.5MPa, and then impregnated for 25 minutes, filtered and dried to obtain modified nano-silica. The added mass ratio of nano-silica to the impregnation solution was 1:7.

[0042] Preparation Example 6 A method for preparing modified nano-silicon dioxide comprises the following steps: 10kg of polyisopropylacrylamide, 3kg of sodium polystyrene sulfonate, 2kg of glutamic acid and 6kg of 2-aminobenzoic acid were mixed with 15kg of methanol and 8kg of water, and the mixture was heated to 45°C and stirred until completely dissolved to obtain an impregnation solution. Nano-silica was then added under stirring, stirred and pressurized to 0.4MPa, and then impregnated for 30 minutes, filtered and dried to obtain modified nano-silica. The added mass ratio of nano-silica to the impregnation solution was 1:6.

[0043] Preparation Example 7 A method for preparing modified nano-silicon dioxide comprises the following steps: 20kg of polyisopropylacrylamide, 8kg of sodium polystyrene sulfonate, 5kg of glutamic acid and 10kg of 2-aminobenzoic acid were mixed with 20kg of methanol and 15kg of water, and the mixture was heated to 50°C and stirred until completely dissolved to obtain an impregnation solution. Then, nano-silicon dioxide was added under stirring, stirred and pressurized to 0.6MPa, and then the mixture was impregnated for 20 minutes and then filtered and dried to obtain modified nano-silicon dioxide. The added mass ratio of nano-silicon dioxide to the impregnation solution was 1:8.

[0044] Comparative Preparation Example 1 A method for preparing modified nano-silica is carried out according to the method in Preparation Example 5, except that 2-aminobenzoic acid is not added to the raw materials.

[0045] Comparative Preparation Example 2 A method for preparing modified nano-silicon dioxide is carried out according to the method in Preparation Example 5, except that sodium polystyrene sulfonate is not added to the raw materials.

[0046] The polyester fiber scraps in the following preparation examples are obtained by crushing waste yarns etc. generated during the processing of polyester fibers into textile products.

[0047] Preparation Example 8 A method for preparing a hydroxyl-modified polyester fiber comprises the following steps: Polyester fiber scraps and glass fibers were mixed in a mass ratio of 1:0.15 to obtain mixed fibers, and then the mixed fibers were immersed in hydrogen peroxide, the mass ratio of the mixed fibers to hydrogen peroxide was 1:1.5, the immersion temperature was 55°C, hydroxyethyl acrylate and methyl methacrylate were added after immersion for 15 minutes, and the mixture was reacted at 70°C for 1.5 hours, then cooled, filtered, washed and dried to obtain hydroxy-modified polyester fibers, and the mass ratio of the mixed fibers to hydroxyethyl acrylate and methyl methacrylate was 1:0.45:0.15.

[0048] Preparation Example 9 A method for preparing a hydroxyl-modified polyester fiber comprises the following steps: Polyester fiber scraps and glass fiber are mixed in a mass ratio of 1:0.1 to obtain mixed fibers, and then the mixed fibers are immersed in hydrogen peroxide, the added mass ratio of the mixed fibers to hydrogen peroxide is 1:1, the immersion temperature is 50°C, hydroxyethyl acrylate and methyl methacrylate are added after immersion for 20 minutes, and the mixture is reacted at 65°C for 2 hours, then cooled, filtered, washed and dried to obtain hydroxy-modified polyester fibers, and the added mass ratio of the mixed fibers to hydroxyethyl acrylate and methyl methacrylate is 1:0.4:0.1.

[0049] Preparation Example 10 A method for preparing a hydroxyl-modified polyester fiber comprises the following steps: Polyester fiber scraps and glass fibers were mixed in a mass ratio of 1:0.2 to obtain mixed fibers, and then the mixed fibers were immersed in hydrogen peroxide, the mass ratio of the mixed fibers to hydrogen peroxide was 1:2, the immersion temperature was 60°C, hydroxyethyl acrylate and methyl methacrylate were added after immersion for 10 minutes, and the mixture was reacted at 75°C for 1 hour, then cooled, filtered, washed and dried to obtain hydroxy-modified polyester fibers, and the mass ratio of the mixed fibers to hydroxyethyl acrylate and methyl methacrylate was 1:0.5:0.2.

[0050] Preparation Example 11 A method for preparing a hydroxyl-modified polyester fiber is carried out according to the method in Preparation Example 10, except that methyl methacrylate is not added.

[0051] Example 1 A method for preparing regenerated asphalt concrete comprises the following steps: S1. Preheating 90 kg of waste asphalt mixture at 120° C. for 15 min to obtain preheated waste asphalt mixture; 25 kg of aggregate and 10 kg of mineral powder were mixed and preheated at 130°C for 8 min to obtain preheated aggregate; S2, preheating 15 kg of base asphalt at 150° C. for 8 minutes and mixing it with the preheated aggregate to prepare a primary mixture; S3, preheating 5 kg of the regeneration agent at 115° C. for 5 min, mixing it with the primary mixture, and then mixing it with the preheated waste asphalt mixture to obtain a mixture; S4. 12 kg of hydroxyl-modified polyester fiber, 15 kg of polymer composite modifier and 5 kg of modified nano-silicon dioxide are mixed and then stirred with the mixture to obtain recycled asphalt concrete.

[0052] In step S1, the waste asphalt mixture is crushed and sieved from the asphalt pavement material obtained by milling to obtain waste asphalt mixtures with particle sizes of 5-10 mm, 15-20 mm and 25-30 mm, and the waste asphalt mixtures with particle sizes of 5-10 mm, 15-20 mm and 25-30 mm are mixed in a ratio of 1:1.3:0.5 to obtain the waste asphalt mixture; The aggregates are slag and crushed stone with a mass ratio of 1:2.5, the crushed stone is 5-15mm continuous particle size crushed stone; the mineral powder is S95 mineral powder; In step S2, the base asphalt is selected from petroleum asphalt, specifically 70# road petroleum asphalt; In step S3, the regeneration agent includes mesophase asphalt, tung oil and penetrant in a mass ratio of 1:1.8:0.08:0.08:0.08, a light stabilizer and an antioxidant, wherein the antioxidant is 2,2-methylenebis-(4-methyl-6-tert-butylphenol), the light stabilizer is hindered amine light stabilizer UV-622, and the penetrant is alkylphenol polyoxyethylene ether, specifically octylphenol polyoxyethylene ether; In step S4, the polymer composite modifier is obtained by mixing SBS powder (SBS-792E produced by Jinan Shanhai Chemical Technology Co., Ltd.) and the porous acrylate copolymer prepared in Preparation Example 1 in a mass ratio of 1:0.7, the modified nano-silica is the modified nano-silica prepared in Preparation Example 5, and the hydroxyl-modified polyester fiber is the hydroxyl-modified polyester fiber prepared in Preparation Example 8.

[0053] Example 2 A method for preparing regenerated asphalt concrete comprises the following steps: S1. Preheating 80 kg of waste asphalt mixture at 110° C. for 20 min to obtain preheated waste asphalt mixture; 20 kg of aggregate and 5 kg of mineral powder were mixed and preheated at 120°C for 10 min to obtain preheated aggregate; S2, preheating 10 kg of base asphalt at 140° C. for 10 min and mixing it with the preheated aggregate to prepare a primary mixture; S3, preheating 3 kg of the regeneration agent at 110° C. for 3 min, mixing the regeneration agent with the primary mixture, and then mixing the regeneration agent with the preheated waste asphalt mixture to obtain a mixture; S4. 8 kg of hydroxyl-modified polyester fiber, 12 kg of polymer composite modifier and 3 kg of modified nano-silicon dioxide are mixed and then stirred with the mixture to obtain recycled asphalt concrete.

[0054] In step S1, the waste asphalt mixture is crushed and sieved from the asphalt pavement material obtained by milling to obtain waste asphalt mixtures with particle sizes of 5-10 mm, 15-20 mm and 25-30 mm, and the waste asphalt mixtures with particle sizes of 5-10 mm, 15-20 mm and 25-30 mm are mixed in a ratio of 1:1.2:0.5 to obtain the waste asphalt mixture; The aggregates are slag and crushed stone with a mass ratio of 1:2. The crushed stone is crushed stone with a continuous particle size of 5-15mm. The mineral powder is S95 mineral powder. In step S2, the base asphalt is selected from petroleum asphalt, specifically 70# road petroleum asphalt; In step S3, the regeneration agent includes mesophase asphalt, tung oil and penetrant, as well as a light stabilizer and an antioxidant in a mass ratio of 1:1.5:0.05:0.05:0.05, the antioxidant is 2,2-methylenebis-(4-methyl-6-tert-butylphenol), the light stabilizer is hindered amine light stabilizer UV-622, and the penetrant is alkylphenol polyoxyethylene ether, specifically octylphenol polyoxyethylene ether; In step S4, the polymer composite modifier is obtained by mixing SBS powder (SBS-792E produced by Jinan Shanhai Chemical Technology Co., Ltd.) and the porous acrylate copolymer prepared in Preparation Example 2 in a mass ratio of 1:0.6, the modified nano-silica is the modified nano-silica prepared in Preparation Example 6, and the hydroxyl-modified polyester fiber is the hydroxyl-modified polyester fiber prepared in Preparation Example 9.

[0055] Example 3 A method for preparing regenerated asphalt concrete comprises the following steps: S1. Preheating 100 kg of waste asphalt mixture at 130° C. for 10 min to obtain preheated waste asphalt mixture; 30 kg of aggregate and 12 kg of mineral powder were mixed and preheated at 150°C for 5 min to obtain preheated aggregate; S2, preheating 18 kg of base asphalt at 160° C. for 5 minutes and mixing it with the preheated aggregate to prepare a primary mixture; S3, preheating 8 kg of the regeneration agent at 120° C. for 3 min, mixing it with the primary mixture, and then mixing it with the preheated waste asphalt mixture to obtain a mixture; S4. 15 kg of hydroxyl-modified polyester fiber, 18 kg of polymer composite modifier and 8 kg of modified nano-silicon dioxide are mixed and then stirred with the mixture to obtain recycled asphalt concrete.

[0056] In step S1, the waste asphalt mixture is crushed and sieved from the asphalt pavement material obtained by milling to obtain waste asphalt mixtures with particle sizes of 5-10 mm, 15-20 mm and 25-30 mm, and the waste asphalt mixtures with particle sizes of 5-10 mm, 15-20 mm and 25-30 mm are mixed in a ratio of 1:1.5:0.6 to obtain the waste asphalt mixture; The aggregates are slag and crushed stone with a mass ratio of 1:3, the crushed stone is 5-15mm continuous particle size, and the mineral powder is S95 mineral powder; In step S2, the base asphalt is selected from petroleum asphalt, specifically 70# road petroleum asphalt; In step S3, the regeneration agent includes mesophase asphalt, tung oil and penetrant in a mass ratio of 1:2:0.1:0.1:0.1, a light stabilizer and an antioxidant, wherein the antioxidant is 2,2-methylenebis-(4-methyl-6-tert-butylphenol), the light stabilizer is hindered amine light stabilizer UV-622, and the penetrant is alkylphenol polyoxyethylene ether, specifically octylphenol polyoxyethylene ether; In step S4, the polymer composite modifier is obtained by mixing SBS powder (SBS-792E produced by Jinan Shanhai Chemical Technology Co., Ltd.) and the porous acrylate copolymer prepared in Preparation Example 3 in a mass ratio of 1:0.8, the modified nano-silica is the modified nano-silica prepared in Preparation Example 7, and the hydroxyl-modified polyester fiber is the hydroxyl-modified polyester fiber prepared in Preparation Example 10.

[0057] Example 4 A method for preparing regenerated asphalt concrete is carried out according to the method in Example 1, except that the porous acrylic copolymer in step S4 is the porous acrylic copolymer in Preparation Example 4.

[0058] Example 5 A method for preparing regenerated asphalt concrete is carried out according to the method in Example 1, except that the hydroxyl-modified polyester fiber in step S4 is the hydroxyl-modified polyester fiber prepared in Preparation Example 11.

[0059] Example 6 A method for preparing regenerated asphalt concrete is carried out according to the method in Example 1, except that no mesophase asphalt is added to the regeneration agent.

[0060] Comparative Example 1 A method for preparing regenerated asphalt concrete is carried out according to the method in Example 1, except that in step S4, the hydroxyl-modified polyester fibers are replaced by polyester fibers that are not hydroxyl-modified in equal amounts.

[0061] Comparative Example 2 A method for preparing regenerated asphalt concrete is carried out according to the method in Example 1, except that no porous acrylate copolymer is added to the polymer composite modifier.

[0062] Comparative Example 3 A method for preparing regenerated asphalt concrete is carried out according to the method in Example 1, except that an equal amount of modified nano-silicon dioxide is replaced by nano-silicon dioxide.

[0063] Comparative Example 4 A method for preparing regenerated asphalt concrete is carried out according to the method in Example 1, except that the modified nano-silicon dioxide is replaced by a mixture of nano-silicon dioxide and polyisopropylacrylamide at a mass ratio of 1:0.1.

[0064] Comparative Examples 5-6 A method for preparing regenerated asphalt concrete is carried out according to the method in Example 1, except that the modified nano-silicon dioxide in step S4 is the nano-silicon dioxide prepared in Comparative Preparation Example 1 and Comparative Preparation Example 2, respectively.

[0065] Performance Testing The regenerated asphalt concrete prepared in the examples and comparative examples of the present application was tested for freeze-thaw splitting strength ratio (%) according to method T0729-2000 in JTJ052-2000 "Test Procedures for Asphalt and Asphalt Mixtures for Highway Engineering" to measure its low-temperature crack resistance. The test results are shown in Table 1 below.

[0066] Table 1: Referring to the test results in Table 1 above, it can be seen that the regenerated asphalt concrete prepared in the embodiment of the present application has excellent low-temperature crack resistance. Referring to the test results of Examples 1 and 4, when graphene aerogel is not added when preparing the porous acrylic copolymer in Example 4, its low-temperature crack resistance is reduced. Combined with the test results of Example 5, when only hydroxyl monomer is added without methyl methacrylate during the preparation of hydroxyl-modified polyester fiber, its low-temperature crack resistance is also reduced. The addition of methyl methacrylate helps the combination of hydroxyethyl acrylate and the active free radicals of polyester fiber to improve its performance; referring to the test results of Example 6, it can be seen that when no intermediate phase asphalt is added to the regeneration agent, its low-temperature crack resistance is also reduced. The addition of intermediate phase asphalt, its aromatic hydrocarbons and unsaturated bonds help the regeneration of waste asphalt and improve its performance.

[0067] Combined with the test results of Example 1 and Comparative Example 1, when the polyester fiber in Comparative Example 1 is directly added without hydroxyl modification, its crack resistance is also reduced. Hydroxyl modification helps to form a network structure with the polymer composite modifier and modified nano-silica, further improving its performance. Combined with the test results of Comparative Example 2, when the porous acrylate copolymer is not added, on the one hand, the adhesion performance of the asphalt is affected, and on the other hand, it cannot play a stress buffering role when subjected to external force, and its low-temperature crack resistance is significantly reduced; Combined with the test results of Comparative Examples 3 and 4, when the nano-silica is added without modification, its performance is significantly reduced, and when it is added with the thermosensitive When the materials are added together but not modified, although the addition of the temperature-sensitive material has a certain positive effect on crack resistance, it is still far weaker than that in Example 1. Combined with the test results of Comparative Examples 5 and 6, it can be seen that when the nano-silica is modified, when sodium polystyrene sulfonate or 2-aminobenzoic acid is not added, its crack resistance is significantly reduced. The addition of the above-mentioned modifier substances not only helps to improve the compatibility of nano-silica with the asphalt system, but also the introduction of its sulfonic acid group and amino and carboxyl functional groups in conjunction with the regeneration agent affects the asphalt regeneration performance, and also affects its formation of a network molecular structure with polyester fibers in the system, thereby playing a better anti-cracking effect.

[0068] In addition, the dynamic stability of the recycled asphalt concrete prepared in Example 1 of the present application was measured with reference to T0719-2011 in JTGE20-2011 "Test Procedures for Asphalt and Asphalt Mixtures in Highway Engineering", and the water-immersion Marshall residual stability (60°C) was measured with reference to T0709-2000 "Marshall Stability Test for Asphalt Mixtures". The measurement results are shown in Table 1 below.

[0069] Table 1: Test items Dynamic stability (times / min) Marshall residual stability after immersion in water / % Example 1 6890 88 The recycled asphalt mixture prepared in the examples of the present application also has excellent water stability and anti-rutting ability.

[0070] This specific embodiment is merely an explanation of the present application and is not a limitation of the present application. After reading this specification, those skilled in the art may make modifications to the present embodiment without any creative contribution as needed, but such modifications are protected by the patent law as long as they are within the scope of the claims of the present application.

Claims

1. A regenerated asphalt concrete, characterized in that: It includes the following raw materials in parts by weight: 80-100 parts of waste asphalt mixture, 10-18 parts of base asphalt, 20-30 parts of aggregate, 5-12 parts of mineral powder, 8-15 parts of hydroxyl modified polyester fiber, 12-18 parts of polymer composite modifier, 3-8 parts of modified nano-silicon dioxide and 3-8 parts of regeneration agent; The polymer composite modifier includes SBS powder and porous acrylic copolymer in a mass ratio of 1: (0.6-0.8), and the modified nano-silica is obtained by immersing the nano-silica in an immersion solution containing polyisopropylacrylamide, sodium polystyrene sulfonate, glutamic acid and 2-aminobenzoic acid.

2. The regenerated asphalt concrete according to claim 1, characterized in that: The impregnation solution comprises the following raw materials in parts by weight: 10-20 parts of polyisopropylacrylamide, 3-8 parts of sodium polystyrene sulfonate, 2-5 parts of glutamic acid and 6-10 parts of 2-aminobenzoic acid, 15-20 parts of methanol and 8-15 parts of water.

3. The regenerated asphalt concrete according to claim 2, characterized in that: The modified nano silicon dioxide is prepared by the following method: Mix polyisopropylacrylamide, sodium polystyrene sulfonate, glutamic acid and 2-aminobenzoic acid with methanol and water, heat to 45-50°C, stir until completely dissolved, then add nano-silica under stirring, stir and pressurize to 0.4-0.6MPa, then immerse for 20-30 minutes, filter and dry to obtain modified nano-silica.

4. The regenerated asphalt concrete according to claim 1, characterized in that: The porous acrylate copolymer is prepared by the following method: 1) Mixing γ-methacryloxypropyltrimethoxysilane, solvent A and graphene aerogel, impregnating and drying to obtain pretreated aerogel; 2) Mix acrylate monomer, sodium styrene sulfonate, triethanolamine, acrylamide, initiator, crosslinker, stabilizer, toluene and solvent B to prepare a reaction solution, then add the pretreated aerogel prepared in step 1) and polymerize at 80-90° C. for 2-4 hours to obtain an acrylate copolymer.

5. The regenerated asphalt concrete according to claim 4, characterized in that: During the preparation of the porous acrylic copolymer, each raw material is added according to the following weight parts: 3-7 parts of γ-methacryloxypropyltrimethoxysilane, 30-40 parts of solvent A, 25-35 parts of graphene aerogel, 40-50 parts of acrylate monomer, 10-20 parts of sodium styrene sulfonate, 5-12 parts of triethanolamine, 12-22 parts of acrylamide, 2-6 parts of initiator, 1-3 parts of cross-linking agent, 1-3 parts of stabilizer, 5-10 parts of toluene, and 40-50 parts of solvent B.

6. The regenerated asphalt concrete according to claim 4, characterized in that: The stabilizer is polyvinyl pyrrolidone or polyethylene glycol; The acrylic acid ester monomer is selected from one or more of methyl methacrylate, ethyl acrylate, isobutyl acrylate, and 2-ethylhexyl acrylate; The initiator is selected from one or both of benzoyl peroxide and azobisisobutyronitrile; The cross-linking agent is selected from one or both of ethylene glycol dimethacrylate and trimethylolpropane triacrylate; Solvent A is a mixture of methanol and water in a mass ratio of 1:(1.5-2); Solvent B is a mixture of water and sodium dodecyl sulfate in a mass ratio of 1: (0.1-0.2).

7. The regenerated asphalt concrete according to claim 1, characterized in that: The hydroxyl-modified polyester fiber is prepared by the following method: The polyester fiber scraps and glass fiber are mixed in a mass ratio of 1: (0.1-0.2) to obtain mixed fibers, and then the mixed fibers are immersed in hydrogen peroxide at a temperature of 50-60°C. After immersion for 10-20 minutes, hydroxyethyl acrylate and methyl methacrylate are added, and the mixture is reacted at 65-75°C for 1-2 hours, and then cooled, filtered, washed and dried to obtain hydroxyl-modified polyester fibers.

8. The regenerated asphalt concrete according to claim 7, characterized in that: During the preparation of hydroxy-modified polyester fibers, the mass ratio of the added mixed fibers to hydrogen peroxide is 1:(1-2), and the mixed fibers are soaked after the hydrogen peroxide and water are mixed in a mass ratio of 1:(3-4). The mass ratio of the added mixed fibers to hydroxyethyl acrylate and methyl methacrylate is 1:(0.4-0.5):(0.1-0.2).

9. The regenerated asphalt concrete according to claim 1, characterized in that: The regeneration agent includes mesophase asphalt, tung oil and penetrant as well as light stabilizer and antioxidant in a mass ratio of 1: (1.5-2): (0.4-0.6): (0.05-0.1): (0.05-0.1): (0.05-0.1); The matrix asphalt is selected from one or more of petroleum asphalt and natural asphalt; The aggregate is selected from slag and crushed stone in a mass ratio of 1: (2-3), and the crushed stone is selected from crushed stone with a continuous particle size of 5-15 mm.

10. A method for preparing the regenerated asphalt concrete according to any one of claims 1 to 9, characterized in that: The following steps are involved: S1. Preheating the waste asphalt mixture at 110-130° C. for 10-20 min to obtain a preheated waste asphalt mixture; The aggregate and the mineral powder are mixed and preheated at 120-150°C for 5-10 minutes to obtain preheated aggregate; S2, preheating the base asphalt at 140-160°C for 5-10 minutes and mixing it with the preheated aggregate to prepare a primary mixture; S3, preheating the regeneration agent at 110-120°C for 3-8 minutes and then mixing it with the primary mixture, and then mixing it with the preheated waste asphalt mixture to obtain a mixture; S4. Mix the hydroxyl-modified polyester fiber, the polymer composite modifier and the modified nano-silicon dioxide and stir them with the mixture to obtain recycled asphalt concrete.

Citation Information

Patent Citations

  • Preparation method and application of temperature response material SiO2-poly(N-isopropyl acrylamide)

    CN104017145A

  • Compound normal temperature asphalt modifier and synthetic method thereof

    CN104559256A

  • Highly-absorbent recycled asphalt concrete and preparation process thereof

    CN109678398A

  • Anti-cracking asphalt concrete and preparation process thereof

    CN111153633A

  • Fine-grained high-performance recycled asphalt concrete easy to construct

    CN115286291A

Cited By

  • Fabricated building composite cement board and preparation process thereof

    CN120554072A

  • Thermal recycled asphalt concrete and preparation method thereof

    CN121651769A

  • A hot recycled asphalt concrete and a method of preparing the same

    CN121651769B